Exceptional-point-engineered phonon laser in a cavity magnomechanical system - Tie Wang; Wei Zhang; Ji Cao; Hong-Fu Wang (New Journal of Physics, 2023)
We propose a scheme to engineer phonon laser in a non-Hermitian cavity magnomechanical (CMM) system with dissipative magnon-photon coupling. The exceptional point (EP) (the analog of the $\mathcal{PT}$ -symmetric regime), emerging in the system and changing the properties of photons, magnons, and phonons, can be observed with a tunable dissipative magnon-photon coupling caused by the cavity Lenz’s law. At the EP, we find that a strong nonlinear relation appears between the mechanical amplification factor and the detuning parameter, which results in a dramatic enhancement of magnetostrictive force and mechanical gain, and leading to the highly efficient phonon laser and the ultralow threshold power. Furthermore, EP induced by dissipative coupling is flexible and tunable compared to the $\mathcal{PT}$ -symmetric regime, and the ultralow threshold power phonon laser is immune to the loss rates of the photon and magnon modes. Our scheme provides a theoretical basis for phonon laser in non-Hermitian systems and presents potential applications ranging from preparing coherent phonon sources to operating on-chip functional acoustic devices.